The mediating role of family function in the relationship between stressful life events and depressive symptoms in mid-pregnancy women: a birth cohort study in Wuhan, China - He, Yihan; Zhou, Hui; Luo, Jiyu; Xu, Ao; Qiu, Dongmei; Huang, Haiyun; Peng, Xiaorui; Zhou, Yujia; Xu, Lingyun; Li, Yang; Li, Yuanyuan; Hu, Xiang; et al. (Frontiers in Psychiatry, 2025)
BackgroundIn current research on prenatal depression among pregnant women, the role of family functioning is crucial yet often overlooked. Specifically, in the field of maternal mental health, relatively limited attention has been given to the psychological well-being of women during the second trimester of pregnancy. This study aims to assess the depression, family functioning, and stressful life events of women in their second trimester, and to explore whether family functioning mediates the relationship between stressful events and depressive symptoms.MethodsA questionnaire survey was conducted with 3,386 pregnant women from the Wuhan Healthy Baby Birth Cohort. Participants completed the 10-item Center for Epidemiologic Studies Depression Scale (CESD-10), the Family APGAR Index, and the 18-item Stressful Life Events Scale. Structural equation modeling was applied to analyze the data.ResultsThe findings revealed significant interrelationships among depression, family functioning, and stressful life events. Family functioning was found to partially mediate the relationship between stressful life events and depressive symptoms during the second trimester, explaining 21.9% of the variance.ConclusionsThese findings suggest that improving family functioning and fostering communication can help reduce depressive symptoms during the second trimester, supporting maternal mental health.